Answer:
No it cannot be concluded.
Step-by-step explanation:
The probability of getting the disease in the first attempt is 50%
The probability of getting the disease in the second attempt is 50%
Thus the probability of getting the disease in either of the turns is 50%+50%=100% (which may seem to be true)
BUT
The probability of not getting the disease in the first attempt is 50%
The probability of not getting the disease in the second attempt is 50%
Thus the probability of not getting the disease in either of the turns is 50%+50%=100% (which is also true for this case)
Thus the probability of getting the disease in either of the 2 contacts is still 50%
Answer: 0.368421053
Step-by-step explanation: 19/7=0.368412053 :-)
Answer:
![\frac{{y}^{2}+13y-6}{{(y-1)}^{2}(y+7)}](https://tex.z-dn.net/?f=%5Cfrac%7B%7By%7D%5E%7B2%7D%2B13y-6%7D%7B%7B%28y-1%29%7D%5E%7B2%7D%28y%2B7%29%7D)
Step-by-step explanation:
1) Rewrite
in the form
, where a = y and b = 1.
![\frac{y}{{y}^{2}-2(y)(1)+{1}^{2}}+\frac{6}{{y}^{2}+6y-7}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B%7By%7D%5E%7B2%7D-2%28y%29%281%29%2B%7B1%7D%5E%7B2%7D%7D%2B%5Cfrac%7B6%7D%7B%7By%7D%5E%7B2%7D%2B6y-7%7D)
2) Use Square of Difference:
.
![\frac{y}{{(y-1)}^{2}}+\frac{6}{{y}^{2}+6y-7}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B%7B%28y-1%29%7D%5E%7B2%7D%7D%2B%5Cfrac%7B6%7D%7B%7By%7D%5E%7B2%7D%2B6y-7%7D)
3) Factor
.
1 - Ask: Which two numbers add up to 6 and multiply to -7?
-1 and 7
2 - Rewrite the expression using the above.
![(y-1)(y-7)](https://tex.z-dn.net/?f=%28y-1%29%28y-7%29)
Outcome/Result: ![\frac{y}{(y-1)^2} +\frac{6}{(y-1)(y+7)}](https://tex.z-dn.net/?f=%5Cfrac%7By%7D%7B%28y-1%29%5E2%7D%20%2B%5Cfrac%7B6%7D%7B%28y-1%29%28y%2B7%29%7D)
4) Rewrite the expression with a common denominator.
![\frac{y(y+7)+6(y-1)}{{(y-1)}^{2}(y+7)}](https://tex.z-dn.net/?f=%5Cfrac%7By%28y%2B7%29%2B6%28y-1%29%7D%7B%7B%28y-1%29%7D%5E%7B2%7D%28y%2B7%29%7D)
5) Expand.
![\frac{{y}^{2}+7y+6y-6}{{(y-1)}^{2}(y+7)}](https://tex.z-dn.net/?f=%5Cfrac%7B%7By%7D%5E%7B2%7D%2B7y%2B6y-6%7D%7B%7B%28y-1%29%7D%5E%7B2%7D%28y%2B7%29%7D)
6) Collect like terms.
![\frac{{y}^{2}+(7y+6y)-6}{{(y-1)}^{2}(y+7)}](https://tex.z-dn.net/?f=%5Cfrac%7B%7By%7D%5E%7B2%7D%2B%287y%2B6y%29-6%7D%7B%7B%28y-1%29%7D%5E%7B2%7D%28y%2B7%29%7D)
7) Simplify
to ![{y}^{2}+13y-6y](https://tex.z-dn.net/?f=%7By%7D%5E%7B2%7D%2B13y-6y)
![\frac{{y}^{2}+13y-6}{{(y-1)}^{2}(y+7)}](https://tex.z-dn.net/?f=%5Cfrac%7B%7By%7D%5E%7B2%7D%2B13y-6%7D%7B%7B%28y-1%29%7D%5E%7B2%7D%28y%2B7%29%7D)
Answer:
![\boxed{\text{1. y + 5 = -4(x - 3); \qquad 2. y - 8 = x + 1}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Ctext%7B1.%20y%20%2B%205%20%3D%20-4%28x%20-%203%29%3B%20%5Cqquad%202.%20y%20-%208%20%3D%20x%20%2B%201%7D%7D)
Step-by-step explanation:
Question 1
The point-slope formula for a straight line is
y – y₁ = m(x – x₁)
x₁ = 3; y₁ = -5; m = -4
Substitute the values
![\boxed{\textbf{y + 5 = -4(x - 3)}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Ctextbf%7By%20%2B%205%20%3D%20-4%28x%20-%203%29%7D%7D)
The diagram shows the graph of equation 1 (red) with slope -4 passing through (3,-5).
Question 2
x₁ = -1; y₁ = 8; m = 1
Substitute the values
![\boxed{\textbf{y - 8 = x + 1}}](https://tex.z-dn.net/?f=%5Cboxed%7B%5Ctextbf%7By%20-%208%20%3D%20x%20%2B%201%7D%7D)
The diagram shows the graph of equation 2 (green) with slope 1 passing through (-1,8).
1,132 people came to watch the balloon festival.